Is this rock pool suitable habitat? Fish diversity in intertidal rock pools of El Zonte, El Salvador - Saúl González-Murcia; Sandra Erdmann; Raquel Alvarado-Larios (Revista Mexicana de Biodiversidad)
Occurrence, abundance, and distribution of fishes in intertidal rock pools are influenced by environmental and biological traits that determine habitat quality. Fishes actively inhabit areas that represent the most suitable habitat for their development. For the intertidal fish community of El Zonte, physical and structural traits of rock pool habitat, as well as habitat complexity, were examined in relation to fish occurrence, abundance, species richness, and body length. Fish occurred in only 18 (40%) of 45 rock pools. A total 309 fish representing 9 species were recorded. The most abundant species were Bathygobius ramosus (160 individuals, 52%) and Abudefduf concolor (88 individuals, 28%). Fishes were absent in rock pools of volumes less than 0.29 m3 and with surface roughness lower than 4.7%. Rock pool volume and surface roughness were related to fish abundance and species richness. Surface roughness was more important to fish abundance and species richness in rock pools of small volumes, but its contribution was limited in larger rock pools. Fish length and rock pool volume were also related, with larger fish generally occurring in larger rock pools. This study presents insights into the factors influencing fish occurrence in tropical intertidal rock pool systems of the Tropical Eastern Pacific.